FACULTY IMPROVEMENT IN VENEZUELAN UNIVERSITIES: A PROPOSAL FOR THE DESIGN AND IMPLEMENTATION OF A DEVELOPMENT PROGRAM - Chacín, Migdy N. (2007)
Venezuelan universities develop in a changing and globalized word. They must fulfill what has been established in governmental policies regarding faculty development. This paper proposes a model for faculty development based on individual and societal needs.Design and implementation stages of the program are described in detail and followed by discussion of the importance of enough government support, university leaders’ commitment to efficient administration of funds and the implementation of programs that produced the changes needed by society.